2009
DOI: 10.1002/hipo.20630
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the cell adhesion protein neuroligin‐1 induces learning deficits and impairs synaptic plasticity by altering the ratio of excitation to inhibition in the hippocampus

Abstract: Trans-synaptic cell-adhesion molecules have been implicated in regulating CNS synaptogenesis. Among these, the Neuroligin (NL) family (NLs 1-4) of postsynaptic adhesion proteins has been shown to promote the development and specification of excitatory versus inhibitory synapses. NLs form a heterophilic complex with the presynaptic transmembrane protein Neurexin (NRX). A differential association of NLs with postsynaptic scaffolding proteins and NRX isoforms has been suggested to regulate the ratio of excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 82 publications
(99 reference statements)
5
116
1
Order By: Relevance
“…These results were confirmed in CA3 pyramidal neurons in an organotypic hippocampal network by using expression of a dominant-negative N-cadherin mutant protein that induces mislocalization of catenins (20). In line with our results on the cooperation of the N-cadherin/catenin and the neuroligin-1 adhesion systems, recent studies in neuroligin-1 knockout mice and in neuroligin-1 overexpressing mice demonstrated an in vivo role of neuroligin-1 in glutamatergic synapse maturation including presynaptic vesicle clustering (12,13,36).…”
Section: Discussionsupporting
confidence: 89%
“…These results were confirmed in CA3 pyramidal neurons in an organotypic hippocampal network by using expression of a dominant-negative N-cadherin mutant protein that induces mislocalization of catenins (20). In line with our results on the cooperation of the N-cadherin/catenin and the neuroligin-1 adhesion systems, recent studies in neuroligin-1 knockout mice and in neuroligin-1 overexpressing mice demonstrated an in vivo role of neuroligin-1 in glutamatergic synapse maturation including presynaptic vesicle clustering (12,13,36).…”
Section: Discussionsupporting
confidence: 89%
“…NLGN1-overexpressing mice show significant deficits in memory acquisition, altered dendritic spine morphology, and higher excitation to inhibition ratio in the hippocampus [66]. On the other hand, some of ASD-related mutations in NLGNs genes lead to intracellular retention of neuroligins [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, neuroligins expressed in non-neuronal cells can induce presynaptic differentiation in axons that contact them (Scheiffele et al 2000) and, conversely, neurexins expressed in non-neuronal cells can induce postsynaptic structures in co-cultured neurons (Graf et al 2004;Nam and Chen 2005). Further, it has been shown that alterations in the balance of excitatory and inhibitory activity can be differentially affected by different neuroligin isoforms (Chih et al 2005;Chubykin et al 2007;Dahlhaus et al 2010). The suitability of this system for providing a code for synapse specification has been discussed (Boucard et al 2005;Dean and Dresbach 2006;Missler and Südhof 1998;Rowen et al 2002;Siddiqui et al 2010;Südhof 2008).…”
mentioning
confidence: 94%
“…The selective effects of neuroligin 1 and 2 in increasing synapse efficacy are dependent on neural activity (Chubykin et al 2007), as is the effect of neuroligin 1 on presynaptic maturation (Wittenmayer et al 2009). Neuroligin manipulation alters the ratio of excitation and inhibition expressed in the hippocampus (Dahlhaus et al 2010). Some changes produced by activity or depolarization are calcium dependent (Rozic-Kotliroff and Zisapel 2007) and NX1 turnover is slowed down by neural activity (Fu and Huang 2010).…”
mentioning
confidence: 99%